2002
DOI: 10.1016/s0006-3495(02)73918-0
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and Intrinsic Tilt of a Tryptophan-Anchored Transmembrane α-Helix Determined by 2H NMR

Abstract: We used solid-state deuterium NMR spectroscopy and an approach involving geometric analysis of labeled alanines (GALA method) to examine the structure and orientation of a designed synthetic hydrophobic, membrane-spanning alpha-helical peptide in phosphatidylcholine (PC) bilayers. The 19-amino-acid peptide consists of an alternating leucine and alanine core, flanked by tryptophans that serve as interfacial anchors: acetyl-GWW(LA)(6)LWWA-ethanolamine (WALP19). A single deuterium-labeled alanine was introduced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
448
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 166 publications
(479 citation statements)
references
References 40 publications
(46 reference statements)
29
448
2
Order By: Relevance
“…[19][20][21]49 We have neglected the possibility of the cylindrical inclusions to tilt. While tilt has been suggested to occur for positive mismatch 3 a recent study 50 showed that modifications in the degree of hydrophobic mismatch need not necessarily affect the tilt angle of a single transmembrane peptide. Hence, it is currently not clear whether experimentally observed tilt of membrane inclusions is induced by hydrophobic mismatch or whether it is an intrinsic property that arises from an asymmetry of the inclusion itself.…”
Section: Single Isolated Inclusionmentioning
confidence: 99%
“…[19][20][21]49 We have neglected the possibility of the cylindrical inclusions to tilt. While tilt has been suggested to occur for positive mismatch 3 a recent study 50 showed that modifications in the degree of hydrophobic mismatch need not necessarily affect the tilt angle of a single transmembrane peptide. Hence, it is currently not clear whether experimentally observed tilt of membrane inclusions is induced by hydrophobic mismatch or whether it is an intrinsic property that arises from an asymmetry of the inclusion itself.…”
Section: Single Isolated Inclusionmentioning
confidence: 99%
“…The proper alignment of the lipid bilayers in each glass plate sample was confirmed by 31 P NMR measurements as described in Ref. 40. The 2 H experiments were done using a quadrupolar echo pulse sequence (41) with an echo delay of 65 s, 1.5 million scans, and with 30-ms interpulse time.…”
Section: Solid State 2 H Nmrmentioning
confidence: 99%
“…This method, called geometric analysis of labeled alanines (GALA), allows for very accurate determination of tilt angles of WALP peptides in either oriented or nonoriented PC bilayers (11,14). In addition, the direction in which the peptides are tilted, as determined by their 1 Abbreviations: PC, phosphatidylcholine; NMR, nuclear magnetic resonance; TFA, trifluoroacetic acid; TFE, 2,2,2-trifluoroethanol; HEPES, N-(2-hydroxyethyl)piperazine-N′-2-ethanesulfonic acid; tBu, tert-butyl; d 4-Ala, deuterated L-alanine-d4; Fmoc, 9-fluorenylmethyloxycarbonyl; di-C12:0-PC, 1,2-dilauroyl-sn-glycero-3-phosphocholine; di-C13:0-PC, 1,2-ditridecanoyl-sn-glycero-3-phosphocholine; di-C14: 0-PC, 1,2-dimyristoyl-sn-glycero-3-phosphocholine; di-C18:1-PC, 1,2-dioleoyl-sn-glycero-3-phosphocholine.…”
Section: Reviewed In Refs 2-4)mentioning
confidence: 99%
“…As in (11), the splitting of the backbone deuteron could not be observed, and the 2 H NMR signals were assigned to the deuterons of the alanine side chain methyl group. The data were fitted to a model R-helix, similar to that in previous studies (10,11,14,16). In particular, data were fitted to the equation ∆ν q is the quadrupolar splitting as measured in unoriented samples.…”
Section: Nmr Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation